Correlation between measured and calculated free phenytoin serum concentration in neurointensive care patients with hypoalbuminemia - Javadi SS; Mahjub R; Taher A; Mohammadi Y; Mehrpooya M (Dove Medical Press, 2018)
Seyyede-Sareh Javadi,1 Reza Mahjub,2 Abbas Taher,3 Younes Mohammadi,4 Maryam Mehrpooya1 1Department of Clinical Pharmacy, School of Pharmacy, Hamadan University of Medical Sciences, Hamadan, Iran; 2Department of Pharmaceutics, School of Pharmacy, Hamadan University of Medical Sciences, Hamadan, Iran; 3Department of Anesthesiology and Critical Care, Hamadan University of Medical Sciences, Hamadan, Iran; 4Modeling of Noncommunicable Diseases Research Center, School of Public Health, Hamadan University of Medical Sciences, Hamadan, Iran Purpose: In critically ill patients, monitoring free phenytoin concentration is a valuable method for phenytoin-dosage adjustment. However, due to technical difficulties and the high cost of these methods, the Sheiner–Tozer equation is routinely used for estimating free phenytoin concentration in clinical practice. There have been conflicting results concerning accuracy and precision of the Sheiner–Tozer equation for prediction of free phenytoin concentration in various patient populations. Therefore, this study was conducted to evaluate the accuracy and correlation of measured and calculated free phenytoin concentrations in neurointensive care patients with hypoalbuminemia. Methods: A total of 65 adult neurointensive care patients with hypoalbuminemia who were receiving phenytoin for prevention or treatment of seizures were recruited in this study. In addition to measuring free phenytoin concentration by HPLC, free phenytoin concentration was calculated using both conventional and revised Sheiner–Tozer equations. Eventually, the correlation and level of agreement between measured and calculated free phenytoin concentrations were evaluated. Results: The mean albumin concentration of studied patients was 2.63±0.57 g/dL. There was a significant but weak–moderate correlation between measured and calculated free phenytoin concentration using conventional and revised Sheiner–Tozer equations (r=0.45 and r=0.43, respectively). Conventional and revised Sheiner–Tozer equations were not able to predict free phenytoin concentrations accurately in 33.85% and 35.4% of patients, respectively. Although the sex of patients did not have a significant impact on the level of agreement, younger patients had a higher level of agreement. Conclusion: Although there was a moderate correlation between calculated and measured free phenytoin concentration, the Sheiner–Tozer equation was not able to predict free phenytoin concentration accurately in all patients, especially in older patients. Therefore, monitoring free phenytoin serum concentration besides clinical outcomes should be considered for phenytoin-dose adjustment in critically ill patients. Keywords: phenytoin, therapeutic drug monitoring, intensive care patients, Sheiner–Tozer equation